Análise físico-química e microbiológica de água em residências localizadas no município de Pacaembu/SP - Yasui, Júlio Cesar (2015)
Industrial development and the uncontrolled growth of large centers caused in recent decades, intensive use of water, causing a strain on water resources, monitoring their quality making it necessary. Maintain water quality within the standards required by the legislation is a guarantee that the consumption of it do not bring risks to health. The collection system, treatment and water supply in the city of Pacaembu / SP is municipal responsibility, so it must ensure that the water meets the quality and potability standards required by Decree No. 2,914 / 11 of the Ministry of Health. In this work evaluated the physical, chemical and microbiological parameters of the water distributed by the municipal supply system in 5 homes during the months of April, May and June 2014, check if it was suitable for consumption by comparison with current legislation. The results show that the physico-chemical parameters are within the limits required by law, and we observed that the residual chlorine concentration values were reduced in the outer points. The microbiological parameters were negative for total and fecal coliforms, and the heterotrophic bacteria count was found inside the gate of the limit, indicating that the water distributed by the supply system is suitable for human consumption and that their properties are being saved from treatment until the building connections.